The Important Role Teaching Pragmatics Plays in Translation Classes:with Reference to Translation Teachers’ Questionnaire - TRIKI, Manel (Journal of Human Sciences, 2015)
There can be no doubt that translation students need to know a good deal about grammar, rhetoric, terminology, and semantics in order to be competent translators. However, students also need to be knowledgeable at the pragmatic level which is totally neglected by most translation teachers in the department of translation in Constantine University 1, Algeria. Thus, this paper attempts to shed light on translation teachers evaluation of the pragmatic knowledge and competence of translation students. The main aim of this paper is to show how important pragmatics is to translation students. In an attempt to realize the aim of this paper a questionnaire was given to twelve translation teachers. The questionnaire findings show that almost all translation students suffer from incompetence at the pragmatic level.